Dependence of interatomic decay widths on the symmetry of the decaying state: analytical expressions and ab initio results - Gokhberg, Kirill; Kopelke, Sören; Kryzhevoi, Nikolai V.; Kolorenč, Přemysl; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
In this article, we investigate the dependence of interatomic Coulombic decay widths on the symmetry of the decaying state. In this type of decay, excited, ionized, and doubly ionized states of an atom or molecule can efficiently relax by ionizing their environment. We concentrate on an atom A and a neighboring atom B and consider such excited, ionized, or doubly ionized states of A that decay by emitting a single photon if A were an isolated atom. Analytical expressions for the various widths are derived for large interatomic distances R. A pronounced dependence of the widths on the symmetry properties of the decaying state is found. This dependence at large R is related to the dependence of the interaction energy of two classical dipoles on their mutual orientation. Comparison with precise ab initio calculations shows that the analytical results hold well at large R, while they deviate from the ab initio values at smaller R due to the effect of orbital overlap.